Anti Microbial Resistance in Salmonella - Yashpal Singh; Anjani Saxena; Jeetendrasingh Bohra; Rajesh Kumar; Avdesh Kumar; Mumtesh Kumar Saxena (Journal of Basic & Applied Sciences, 2019)
Antibiotics are one of the major drugs to eradicate microbial infection. Many types of antibiotics have been used as therapeutics in several fields such as medical, agriculture, animal husbandry for human beings as well as animals. In past few years microbes have become resistant to some common antibiotics. We found that drug resistance is escalating at an alarming rate. Some of the infections like typhoid, pneumonia, tuberculosis, and gonorrhea are becoming difficult to treat while antibiotics are becoming less effective. Typhoid fever is one of the most common foodborne illnesses leading to many deaths annually worldwide. The emergence of multi-drug resistant Salmonella enterica serovar Typhi strains (S. Typhi) has resulted in several large outbreaks of enteric fever in many developing countries of the world leading to increased morbidity and mortality. Multi-drug resistance remains a major public health problem, particularly in developing countries of Asia and Africa. Some important measures like rational use of antibiotics, improvement in public sanitation facilities, availability of clean drinking water, promotion of safe food handling practices and public health education can play a crucial role in the prevention of multiple drug resistant typhoid fever.